Feline hemotropic mycoplasmosis concurrent with bacterial cystitis in a domestic shorthair cat - Hemasri, Sukumaran; Okene, Ibrahim Abdul-Azeez; Goni, Mohammed Dauda (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: The main aim of this case report is to present a case of feline hemotropic mycoplasmosis that occurred concurrently with bacterial cystitis following the bite. Material and methods: A 3-year-old intact male domestic shorthair cat weighing 3.7 kg was referred to the Universiti Malaysia Kelantan Veterinary Clinic with clinical signs of hematuria and dysuria. History revealed that it was managed outdoor, fed with kibbles and wet food, but with no vaccination and deworming. Upon physical examination, the cat had a dull appearance, pale mucous membrane, normal respiratory rate, hypothermia, and bradycardia. Upon the examination of the urogenital system, there were urine burns at the anal region, necrotized penile tip, and presence of bite wound observed at the perineal region. Turgid and enlarged urinary bladder was identified upon palpation. Results: Diagnostic investigation revealed the hemotropic mycoplasmosis via microscopy, while urine culture was positive for Escherichia coli infection. The cat was successfully treated symptomatically. Conclusion: However, the prognosis of this cat was guarded given that the anemia was unresolved at the point of discharge. http://doi.org/10.5455/javar.2018.e304